Analysis of a disc-loaded circular waveguide for interaction impedance of a gyrotron amplifier - Kesari V.; Jain P.K.; Basu B.N. (My University, 2025)
A rigorous electromagnetic analysis of a circular waveguide loaded with axially periodic annular discs was developed in the fast-wave regime, considering finite axial disc thickness and taking into account the effect of higher order space harmonics in the disc-free region and higher order modal harmonics in the disc-occupied region of the structure. The quality of the disc-loaded circular waveguide was evaluated with respect to its azimuthal interaction impedance that has relevance to the gain of a gyrotron millimeter-wave amplifier (gyro-traveling-wave tube) in which such a loaded waveguide finds application as a wideband interaction structure. The results of electromagnetic analysis of the structure with respect to both the dispersion and azimuthal interaction impedance characteristics were validated against the commercially available code: high frequency structure simulator (HFSS). The analysis predicts that the value of the interaction impedance at a given frequency decreases with the increase of the disc hole radius and disc periodicity. The change of the axial disc thickness does not significantly change the value of the interaction impedance though it shifts the frequency range over which appreciable interaction impedance is obtained. Out of the three disc parameters, namely the disc hole radius, thickness and periodicity, the lattermost is most effective in controlling the value of the azimuthal interaction impedance. However, the passband of frequencies and the center frequency of the passband both decrease with the increase of the disc periodicity. Moreover, the disc periodicity that provides large azimuthal interaction impedance would in general be different from that giving the desired dispersion shape for wideband interaction in a gyro-TWT, suggesting a trade-off in the value of the disc periodicity to be chosen. © 2005 Springer Science+Business Media, Inc.